Thrombophilia does not increase risk for neonatal complications in preterm infants - Kenet, Gili; Maayan-Metzger, Ayala; Rosenberg, Nurit; Sela, Ben-Ami; Mazkereth, Ram; Ifrah, Aviyah; Kuint, Jacob (Thrombosis and Haemostasis, 2003)
The association between thrombophilia and neonatal complications was evaluated in a single-center prospective study. Prevalence of genetic prothrombotic markers (FVL, MTHFR, FIIG20210A) and levels of plasma homocysteine were assayed in 166 premature (mean gestational age: 30.9±2.3 weeks) and low birth weight (mean weight: 1327±319 grams) infants. The incidence of any neonatal complications was compared in infants with and without thrombophilia. A total of 38 infants were defined as “thrombophilic” due to heterozygous FVL (n=4) and/or FIIG20210A (n=8, including one case of combination with FVL) or homozygous 677T MTHFR (n=22) or homo-cysteine plasma levels above 15µmole/liter. Neonatal complications included: small for gestational age (28.8%), respiratory distress syndrome (51.8%), broncho-pulmonary dysplasia (10.2%), patent ductus arteriosus (12.7%), intraventricular hemorrhage (17%), periventricular leucomalacia (8.4%), retinopathy of prematurity (15.1%) and necrotizing enterocolitis in 1.2% of infants. No thrombosis was documented. The prevalence of perinatal complications and the severity of diseases were similar among infants with or without thrombophilia (p=0.564). Our data suggest that preterm infants with thrombophilia are not at increased risk for developing neonatal complications.
Keywords: Homocysteine; neonates; preterms; SGA; thrombophilia